An extensive analysis of Brazil and the Netherlands determinants of football attendance - Matthijs Edel (Socioeconomic Analytics, 2024)
Understanding attendance at football stadiums holds great significance for sports economists and football clubs. Consequently, extensive research has been conducted to analyze the factors influencing football stadium attendance. However, much of this research has been confined to short-term analyses or focused solely on European countries. This study seeks to broaden the scope by examining long-term trends in the Netherlands and exploring the dynamics in Brazil. In the Netherlands, factors such as unemployment and overall interest in football emerge as significant determinants of stadium attendance. Surprisingly, hooliganism does not appear to have a notable impact, and the influence of leisure time is unclear. In the Brazilian context, stadium capacity and goal difference do not show significant effects on attendance, and the impact of the club's division is ambiguous.